REVISITED CULTURAL HERITAGE & ARCHITECTURAL HERITAGE PREFERENCES TO LEVERAGE SUSTAINABLE TOURISM PERFORMANCE: EMPIRICAL RESEARCH ON INDONESIA WORLD HERITAGE SITES - Batu, Kardison Lumban; Almadana, Aulia Vidya (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
Present study investigated the local benevolence uniqueness (LBU) and Aesthetical Environmental Look (AEL) on Sustainable Tourism Performance (STP) mediated by Revisited Cultural Heritage Value (RCHV) & Architectural Heritage Preferences (AHP. Data was gathering through survey with questionnaires based from January to June 2022, also questionnaires were distributed to email as well as other social media platform with google forms. Data collection is gained from the domestics’ tourists who have made traveling more than twice and visiting cultural heritage sites. 500 questionnaires were sent and 400 were returned and 383 could be used for further analysis. with non-purposive sampling and purposive sampling technique, respondents should have made traveling). Structural Equation Modeling (SEM) with AMOS 22 was deployed to analyze data. Statistical outputs demonstrated the research findings showing all the proposed hypotheses have significant impact on sustain tourism performance.